Pengembangan nilai-nilai pendidikan Islam pada bahan ajar ilmu pengetahuan sosial berbasis Learning Clinic di MI NU Al Huda 02 Kecamatan Gebog Kabupaten Kudus - Ali Mahmudi; Lilik Sriyanti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The purpose of this study was to develop the Development of Islamic Education Values in Learning Clinic-Based Social Science Teaching Materials for fifth-grade teachers of Madrasah Ibtidaiyah (MI) MI NU Al Huda 02, Gebog District, Kudus Regency. This research method uses Research and Development (R & D) from Borg and Gall. The model development procedure uses the main stages, namely introduction, design and development, and validation. Sources of data in the form of documentation of the performance of learning assistance by teachers, questionnaires, observations, interviews, and model trials. The results of the study show that learning clinic-based online learning assistance is very important and needed, it is proven that many students experience difficulties in understanding the subject matter due to limited interaction and communication with the teacher so the learning outcomes are low on average of 67.33 or below the KKM score of 75.00 and there is no learning clinic-based online learning model that can help students with learning difficulties. Based on the results of limited trials and expanded trials of using the product, it was described that there was an increase in the quality of teachers' ability to carry out mentoring by 27.50 from limited trials of 60.00% up to 84.50% so that the product could be categorized as effective and suitable for use as a guide by class V teacher. The development product is in the form of a learning clinic-based learning assistance guidebook. The results of the due diligence guidebook from experts and practitioners obtained a value of 83.33 in the very feasible category. Test the effectiveness with the SPSS Paired sample Test t-test in improving student learning outcomes from pretest and post-test data obtained t count 7.434, while p = 0.00 <0.05, then Ha is accepted and Ho is rejected. The conclusion from these results is that there is a real significant difference between learning outcomes in the pretest and posttest. This means that the Development of Islamic Education Values in Learning Clinic-Based Social Science Teaching Materials is effective in increasing student learning outcomes at MI NU Al Huda 02 Padurenan, Gebog District, Kudus Regency